Integrating Biological Advances Into the Clinical Management of Breast Cancer Related Lymphedema - Invernizzi, Marco; Lopez, Gianluca; Michelotti, Anna; Venetis, Konstantinos; Sajjadi, Elham; De Mattos-Arruda, Leticia; Ghidini, Michele; Runza, Letterio; de Sire, Alessandro; Boldorini, Renzo; Fusco, Nicola (Frontiers in Oncology, 2020)
Breast cancer-related lymphedema (BCRL) occurs in a significant number of breast cancer patients as a consequence of the axillary lymphatics’ impairment after therapy (mainly axillary surgery and irradiation). Despite the significant achievements in the diagnosis and treatment of these patients, BCRL is often diagnosed at its occurrence and remains a progressive and irreversible condition in most cases. This has dramatic consequences in terms of breast cancer survivors’ quality of life and on sanitary costs. Despite there are no validated pre-surgical strategies to identify individuals that harbor an increased risk of BCRL, several clinical, therapeutic, and tumor-specific features are recurrent in BCRL patients. Over the past few years, many studies have unraveled the complexity of the molecular and transcriptional events leading to the lymphatic system ontogenesis. Furthermore, novel molecular insights are coming from the study of the germline alterations involved at variable levels in BCRL models. Regrettably, there is a substantial lack of predictive biomarkers for this condition, given that our knowledge of BCRL molecular bases remains too puzzled. The purposes of this review were i) to outline the biology underpinning the ontogenesis of the lymphatic system; ii) to assess the current state of knowledge of the molecular alterations that can be involved in BCRL pathogenesis and progression; iii) to discuss the present and short-term future perspectives in biomarker-based patients’ risk stratification; and iv) provide practical information that can be employed to improve the clinical management of these patients.